Predictors and Outcomes of Health–Related Quality of Life in Adults with CKD - Porter, Anna C. (Clin J Am Soc Nephrol, 2016)
BACKGROUND AND OBJECTIVES: Low health–related quality of life is associated with increased mortality in patients with ESRD. However, little is known about demographic and clinical factors associated with health–related quality of life or its effect on outcomes in adults with CKD. DESIGN, SETTINGS, PARTICIPANTS, & MEASUREMENTS: Data from 3837 adult participants with mild to severe CKD enrolled in the prospective observational Chronic Renal Insufficiency Cohort and Hispanic Chronic Renal Insufficiency Cohort Studies were analyzed. Health–related quality of life was assessed at baseline with the Kidney Disease Quality of Life-36 and its five subscales: mental component summary, physical component summary, burden of kidney disease (burden), effects of kidney disease (effects), and symptoms and problems of kidney disease (symptoms). Low health–related quality of life was defined as baseline score >1 SD below the mean. Using Cox proportional hazards analysis, the relationships between low health–related quality of life and the following outcomes were examined: (1) CKD progression (50% eGFR loss or incident ESRD), (2) incident cardiovascular events, and (3) all-cause death. RESULTS: Younger age, women, low education, diabetes, vascular disease, congestive heart failure, obesity, and lower eGFR were associated with low baseline health–related quality of life (P<0.05). During a median follow-up of 6.2 years, there were 1055 CKD progression events, 841 cardiovascular events, and 694 deaths. Significantly higher crude rates of CKD progression, incident cardiovascular events, and all-cause death were observed among participants with low health–related quality of life in all subscales (P<0.05). In fully adjusted models, low physical component summary, effects, and symptoms subscales were independently associated with a higher risk of incident cardiovascular events and death, whereas low mental component summary was independently associated with a higher risk of death (P<0.05). Low health–related quality of life was not associated with CKD progression. CONCLUSIONS: Low health–related quality of life across several subscales was independently associated with a higher risk of incident cardiovascular events and death but not associated with CKD progression.